Incorporating lower grade toxicity information into dose finding designs - Iasonos, Alexia (2011)
BACKGROUND: Toxicity grades underlie the definition of a dose limiting toxicity (DLT) but in the majority of phase I designs, the information contained in the individual grades is not used. Some authors have argued that it may be more appropriate to consider a polytomous rather than dichotomous response. PURPOSE: We investigate whether the added information on individual grades can improve the operating characteristics of the Continual Reassessment Method (CRM). METHODS: We compare the original CRM design for a binary response with two stage CRM designs which make di erent use of lower-grade toxicity information via simulations. Specifically we study; a two-stage design that utilizes lower-grade toxicities in the first stage only, during the initial non model-based escalation, and two-stage designs where lower grades are used throughout the trial via explicit models. We postulate a model relating the rates of lower grade toxicities to the rate of DLTs, or assume the relative rates of low to high grade toxicities is unknown. The designs were compared in terms of accuracy, patient allocation and precision. RESULTS: Significant gains can be achieved when using grades in the first stage of a two-stage design. Otherwise, only modest improvements are seen when the information on grades is exploited via the use of explicit models, where the parameters are known precisely. CRM with some use of grade information, increases the number of patients treated at the MTD by approximately 5%. The additional information from lower grades can lead to a small increase in the precision of our estimate of the MTD. LIMITATIONS: Our comparisons are not exhaustive and it would be worth studying other models and situations. CONCLUSIONS: Although, the gains in performance were not as great as we had hoped, we observed no cases where the performance of CRM was poorer. Our recommendation is that investigators might consider using graded toxicities at the design stage.